Badan Penyelenggara Jaminan Sosial Ketenagakerajaan Berdasarkan Undang-undang Nomor 40 Tahun 2004 Tentang Sistem Jaminan Sosial Nasional - Andrika, Ahmad; Ahmad, Ibrahim; Tumuhulawa, Arifin (Journal Evidence Of Law, 2023)
The purpose of this study is to determine and analyze the Implementation of Policies Towards the Implementation of the Employment Social Security Program Based on Law Number 40 of 2004 concerning the National Social Security System and to determine and analyze the Form of Application of Administrative Sanctions Against Business Entities or Non-Governmental Institutions That Do Not Run the Employment Social Security Organizing Agency Program. In this study the authors used normative research methods, namely legal research conducted by means of literature review and study of legislation. In this research what is studied is legal events, legal relationships and objects of law. Implementation of Policies on the Implementation of the Employment Social Security Program Based on Law Number 40 of 2004 concerning the National Social Security System, namely the Government, among others, has made implementing regulations of the Act, has also continuously carried out all orders of the legislation. From the implementation of the Law, the labor social security program is a basic protection for workers and their families and can provide legal certainty. However, the practice of charging routine contributions by the BPJS as well as the imposition of sanctions on citizens is what actually denies the main principle of the social security system which should be borne by the state as the principle of the welfare state which is then transferred to the burden of citizens as well as accompanied by sanctions if citizens do not want to register as / participate in insurance organized by BPJS. Thus, it can be said that the Government has not succeeded in implementing the national social security system in realizing community welfare.